Possible Impacts of Climatic Warming on Polar Bears ... - Stirling, I.; Derocher, A.E. (University of Alberta Library, 1993)
If climatic warming occurs, the first impacts on polar bears (Ursus maritirnus) will be felt at the southern limits of their distribution, such as in James and Hudson bays, where the whole population is already forced to fast for approximately four months when the sea ice melts during the summer. Prolonging the ice-free period will increase nutritional stress on this population until they are no longer able tost ore enough fat to survive thicee -free period. Early signs of impact will include declining body condition, lowered reproductive rates, reduced survival of cubs, and an increase in polar bear-human interactions. Although most of these changes are currently detectable in the polar bears of western Hudson Bay, it cannot yet be determined if climatic change is involved. In the High Arctic, a decrease in ice cover may stimulate an initial increase in biological productivity. Eventually however, it is likely that seal populations will decline wherever the quality and availability of breeding habitat are ...